Designs of Biomaterials and Microenvironments for Neuroengineering. (9th December 2018) - Yang, Yanru; Zhang, Yuhua; Chai, Renjie; Gu, Zhongze
Abstract : Recent clinical research on neuroengineering is primarily focused on biocompatible materials, which can be used to provide electroactive and topological cues, regulate the microenvironment, and perform other functions. Novel biomaterials for neuroengineering have been received much attention in the field of research, including graphene, photonic crystals, and organ-on-a-chip. Graphene, which has the advantage of high mechanical strength and chemical stability with the unique electrochemical performance for electrical signal detection and transmission, has significant potential as a conductive scaffolding in the field of medicine. Photonic crystal materials, known as a novel concept in nerve substrates, have provided a new avenue for neuroengineering research because of their unique ordered structure and spectral attributes. The "organ-on-a-chip" systems have shown significant prospects for the developments of the solutions to nerve regeneration by mimicking the microenvironment of nerve tissue. This paper presents a review of current progress in the designs of biomaterials and microenvironments and provides case studies in developing nerve system stents upon these biomaterials. In addition, we compose a conductive patterned compounded biomaterial, which could mimic neuronal microenvironment for neuroengineering by concentrating the advantage of such biomaterials.